Kemunduran dan Kehancuran Kerajaan Safawiyah di Persia - Basri, Muhammad; Lubis, Eka Jelita; Karima; Khairani, Rida (Universitas Islam Internasional Darullughah Wadda'wah, 2023)
The Safavid Daulah is a dynasty that has an important role in Islamic history. The process of the collapse of the Safawiyah Daulah in Persia, after leaving Caliph Abbas I there were six Caliphs who continued the government of the Safawiya Daulah. In its development, the Safavid kingdom continued to experience changes along with changes in positions. There was a prolonged conflict with the Ottoman kingdom, then the moral decadence that hit some of the leaders of the Safavid kingdom, then the weakness of the king who was appointed after King Abbas I. The purpose of writing this article is to find out about the decline and destruction of the Safavid kingdom. This study uses a historical research method which consists of four stages, namely, heuristics, criticism, interpretation and historiography. As a result of this article, it can be found that the history of the decline of the Safawiyah kingdom began with the cracking and breaking of the great pillars that supported the progress of the Safawiyah Kingdom. Like the death of capable kings, as well as kings who had a habit of drinking, civil war, and power struggles. Apart from that, there were also conflicts between kingdoms, the dualism of the Safawiyah kingdoms that existed in other regions, inconsistent succession of rulers, rebellions from outside such as the Sunnis, and the emergence of authority among the ulama.